Compound C Protects Mice from HFD-Induced Obesity and Nonalcoholic Fatty Liver Disease - Fang Wang; Yuxing Liu; Jingjing Yuan; Wenjun Yang; Zhaohui Mo (International Journal of Endocrinology)
Objectives. The aim of this study was to investigate the effects of compound C on an in vivo mouse model of high-fat diet- (HFD-) induced obesity and hepatosteatosis. Methods. C57BL/6 mice were fed with a standard diet (n = 5) for 16 weeks and then injected saline once a day for 4 weeks as the normal chow group. Mice (n = 10) were fed with HFD for 16 weeks to induce obesity and hepatosteatosis and then divided into two groups: HFD + vehicle group injected with the vehicle solution (saline) and HFD + compound C group injected with compound C in saline (5 mg/kg i.p., once a day) for 4 weeks. Liver histology was observed. The expression levels of genes related to lipid metabolism and proinflammation in liver tissue were examined. NLRP3 inflammasome expression in liver tissue was detected by the western blot assay. HepG2 cells were pretreated with compound C and/or AICAR for 1 h and then treated with palmitic acid (PA) for 3 h. The cells were collected, and mRNA levels were determined. Results. There was a significant reduction in body-weight gain and daily food intake in the HFD + compound C group compared with the HFD + vehicle group (p<0.05). The glucose tolerance test (GTT) and insulin tolerance test (ITT) showed that compound C alleviated insulin resistance. Histology analysis showed a significant reduction of hepatic steatosis by compound C. Compound C also significantly decreased fatty acid synthesis genes, while increased fatty acid oxidation genes. Furthermore, compound C significantly reduced the expression of proinflammatory markers and NLRP3 inflammasome (p<0.05). Compound C enhanced mRNA levels of SOD1, SOD2, catalase, GPx1, and GPx4 and reduced the p-AMPK/AMPK ratio, which were stimulated by palmitic acid (PA). The effect was enhanced by AICAR. Conclusion. Our data suggest that compound C is a potent NAFLD suppressor and an attractive therapeutic target for hepatic steatosis and related metabolic disorders.